Increased Incidence of Angiodysplasia of the Gastrointestinal Tract and Bleeding in Patients with Continuous Flow Left Ventricular Assist Devices (LVADs). Issue 7 (July 2013) - Muthiah, Kavitha; Robson, Desiree; Macdonald, Peter S.; Keogh, Anne M.; Kotlyar, Eugene; Granger, Emily; Dhital, Kumud; Spratt, Phillip; Jansz, Paul; Hayward, Christopher S.
Background: Continuous flow left ventricular assist devices (cfLVADs) are used in clinical practice for the management of end-stage heart failure. Axial flow cfLVADS have been associated with increased rates of adverse gastrointestinal events such as bleeding angiodysplasia. The purpose of this study was to determine the incidence of bleeding gastrointestinal tract angiodysplasia and the profile of patients supported with the centrifugal cfLVAD, referred for endoscopy. Methods: A retrospective analysis of 66 patients implanted with Ventrassist (n = 33) and Heartware (n = 33) centrifugal continuous flow LVADs was performed. All patients were on warfarin, aspirin and/or clopidogrel. Endoscopy was performed in all patients with either active gastrointestinal bleeding (n = 6) or anemia with positive fecal occult blood (n = 6). Results: Bleeding gastrointestinal angiodysplasia was demonstrated in 5 out of the 12 (41.6%) patients who underwent endoscopy from the cohort of 66 cfLVAD supported patients (7.6%). The incidence of bleeding angiodysplasia was higher than the age-standardized rate of andiodysplasia from literature (0.8%). Active gastrointestinal bleeding in one other patient was due to diverticulosis. The five patients with bleeding angiodysplasia tended to be older than the remaining 61 patients (58.8 ± 10.3 vs 49.6 ± 15.7 years, p = 0.2). Conclusions: We found excess bleeding angiodysplasia in patients on centrifugal cfLVAD support. It may be appropriate to screen for angiodysplasia particularly in older patients prior to support by centrifugal cf LVADs. Reasons for the higher rate of bleeding angiodysplasia in cfLVAD patients warrant further study.